CRISPR genome engineering and viral gene delivery: a case of mutual attraction - Schmidt, Florian; Grimm, Dirk (Biotechnology journal, 2015)
The adaptation of the CRISPR/Cas9 DNA engineering machinery for mammalian cells has revolutionized our approaches to low- or high-throughput genome annotation and paved the way for conceptually novel therapeutic strategies. A large part of the attraction of CRISPR stems from the small size of its two core components - Cas9 and gRNA - and hence its compatibility with virtually any available viral vector delivery system. As a result, over the past two years, four major classes of viral vectors have already been engineered and applied as CRISPR delivery tools - retroviruses, lentiviruses, adenoviruses, and adeno-associated viruses (AAVs). The juxtaposition of these two technologies reflects a case of tremendous mutual attraction and holds unprecedented promises for biology and medicine. Here, we provide an overview of the state-of-the-art of this rapidly emerging field, from a comparative description of the principal vector designs, to a synopsis of some of the most exciting applications that were reported to date, including the use of viral CRISPR vectors for genome-wide loss-of-function screens, multiplexed gene editing or disease modeling in animals. Once specificity and safety have been improved further, viral vector-mediated in vitro/in vivo CRISPR delivery and expression promise to radically transform basic and applied biomedical research.